1993
DOI: 10.1002/jpln.19931560504
|View full text |Cite
|
Sign up to set email alerts
|

Pflanzenverfügbarkeit der Phosphatvorräte ackerbaulich genutzter Böden. ‐Langfristige Feldversuche zur Nutzbarkeit des Bodenphosphors und zur Bewertung der Bodenuntersuchung ‐

Abstract: Es wird die Frage behandelt, in welchem Maße die in landwirtschaftlich genutzten Böden heute vorhandenen, meist durch frühere Düngung angereicherten Phosphatvorräte pflanzenverfügbar sind, inwieweit sie durch ackerbauliche Nutzung abgebaut werden können und welche P‐Gehalte im Boden für die Ertragsbildung notwendig sind. Hierzu wird über langfristige Feldversuche auf Parabraunerden von pH 6.8 ‐ 7,4 im südniedersächsischen Lößgebiet berichtet, die seit 1977 in Ackerbaubetrieben auf Großparzellen ohne Wiederholu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 10 publications
2
4
0
1
Order By: Relevance
“…Winter wheat was, therefore, more efficient to mobilize even lower soil P reserves. The relatively lower sensitivity of winter wheat compared with the beet crop is in agreement with earlier findings (Jungk et al 1993). It might be ascribed to the differences in root properties of both species.…”
Section: Discussionsupporting
confidence: 93%
“…Winter wheat was, therefore, more efficient to mobilize even lower soil P reserves. The relatively lower sensitivity of winter wheat compared with the beet crop is in agreement with earlier findings (Jungk et al 1993). It might be ascribed to the differences in root properties of both species.…”
Section: Discussionsupporting
confidence: 93%
“…of pH increase, on the recovery of soil and fertilizer P, has also been shown by the work Sturm and Iserman (1978). Similar results have been obtained by Junk et al 1993, and by Kalavrouziotis et al (2008) who found that at pH 7.18 the available Olsen-P of soil was 18.16 mg/kg, while at pH 7.52 the p level increased to 41.16 mg/kg, under the cultivation of Brassica oleracea var. Italica (Broccoli).…”
Section: Calcium Carbonatesupporting
confidence: 90%
“…However, the DL-method is commonly utilised in the Lusatian lignite mining district (Vetterlein et al 1999b) and is equivalent to the often used Bray Method for P determination on open-cast mine spoils (Vetterlein et al 1999a). Despite such fi ndings, Jungk et al (1993) reported that a TSP fertilisation with more than 218 kg P ha -1 was necessary to signifi cantly increase soil available P in order to achieve full yield in a crop rotation with sugar beet, winter weed, or winter barley, even on fertile, arable soil. Such high dosages of P fertiliser have been reported as necessary for soils with a high phosphate adsorption capacity (Jamer et al 1998).…”
Section: P-fertilisation and Nutrient Availabilitymentioning
confidence: 99%